2015
DOI: 10.1371/journal.pone.0144163
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Protein Complexes in Protein Interaction Networks Modeled as Gene Expression Biclusters

Abstract: Developing suitable methods for the detection of protein complexes in protein interaction networks continues to be an intriguing area of research. The importance of this objective originates from the fact that protein complexes are key players in most cellular processes. The more complexes we identify, the better we can understand normal as well as abnormal molecular events. Up till now, various computational methods were designed for this purpose. However, despite their notable performance, questions arise re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Next, we compared our method with DyCluster [ 25 ] in the Tables 10 , 11 , 12 , 13 , 14 and 15 . DyCluster is a framework to detect complexes based on PPI data and gene expression data, which was proposed by Hanna et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we compared our method with DyCluster [ 25 ] in the Tables 10 , 11 , 12 , 13 , 14 and 15 . DyCluster is a framework to detect complexes based on PPI data and gene expression data, which was proposed by Hanna et al .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Hanna et al . proposed a framework termed DyCluster to detect complexes based on PPI networks and gene expression data [ 25 ]. Firstly, DyCluster uses biclustering techniques to model the dynamic aspect of PPI networks by incorporating gene expression data.…”
Section: Introductionmentioning
confidence: 99%
“…It is showed that using a biclustering algorithm to extract some dynamic subnetworks from static PPI networks, improve the accuracy of protein complex detection methods[ 64 ]. To have a better view of the proposed genetic-based algorithm advantages, in this subsection, we compare our proposed biclustering method, GA-DCT, with some popular biclustering algorithms CC[ 39 ], BiMax[ 44 ], xMOTISs[ 46 ], OPSM[ 47 ],ISA[ 48 ] and UniBic[ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al [25] introduced a semi-supervised learning method based on neural network that uses biological and topological feature vectors. The DyCluster [26] method utilized the gene expression data for detection of a protein complex. A number of computational approaches along with their frameworks and feature sets are depicted in Table 1.…”
Section: Introductionmentioning
confidence: 99%